Revitalisasi hukum waris Islam dalam penyelesaian kasus sengketa tanah waris pada masyarakat Sasak - Lalu Supriadi Bin Mujib (State Institute of Islamic Studies (IAIN) Salatiga, 2019)
The inheritance issue is considered crucial to evaluate since it is closely related to inheritance transfer from the deceased to the living family and death is natural and common phenomenon. This research aims to investigate the inheritance legal system, the factors influencing the land dispute cases and the revitalization of Islamic legal system to reach a settlement of this land dispute issues. This field research employs qualitative approach using field and library research with socio-legal approach. The research data is categorized into two, primary and secondary data. The data was obtained using observation technique, interview, and doccumentation. The results indicate that: First, the distribution of inheritance land is conducted in different ways such as grants,, discussion, and faraid. Second, the factors influencing the land dispute cases are greed and lack of information about inheritance legal system, so the society do not know the legal system related to the inheritance. Third, revitalization is important because it is ruled out in Islamic teachings and is considered absolute for Islam society. This research conludes that Islamic Inheritance legal system is the best alternative to reach a settlement of land disputes in Sasak community.